2011
DOI: 10.1002/jmv.21993
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic and virulence analysis of tick‐borne encephalitis virus field isolates from Switzerland

Abstract: Tick-borne encephalitis (TBE) is an endemic disease in Switzerland, with about 110-120 reported human cases each year. Endemic areas are found throughout the country. However, the viruses circulating in Switzerland have not been characterized so far. In this study, the complete envelope (E) protein sequences and phylogenetic classification of 72 TBE viruses found in Ixodes ricinus ticks sampled at 39 foci throughout Switzerland were analyzed. All isolates belonged to the European subtype and were highly relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 34 publications
4
19
0
3
Order By: Relevance
“…In our previous study, we had shown that all tick-derived TBEV isolates from the canton of Valais belonged to the European subtype [45]. In vivo and in vitro studies of Swiss TBEV isolates suggest a high number of avirulent isolates, which is in agreement with a high proportion of subclinical or mild TBE infections in the Swiss public [53]. …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In our previous study, we had shown that all tick-derived TBEV isolates from the canton of Valais belonged to the European subtype [45]. In vivo and in vitro studies of Swiss TBEV isolates suggest a high number of avirulent isolates, which is in agreement with a high proportion of subclinical or mild TBE infections in the Swiss public [53]. …”
Section: Discussionmentioning
confidence: 71%
“…The European subtype is the least virulent subtype and is responsible for all human cases of TBE in Western Europe. In Switzerland, TBEV isolates circulating in ticks collected at 39 foci were closely related and all of them belonged to the European subtype [53]. In our previous study, we had shown that all tick-derived TBEV isolates from the canton of Valais belonged to the European subtype [45].…”
Section: Discussionmentioning
confidence: 99%
“…Within such foci, several genetic variants of TBEV have been identified [6][12]. Furthermore, several studies have identified geographical clustering of specific TBEV variants within small geographic areas [6][8].…”
Section: Introductionmentioning
confidence: 99%
“…Within such foci, several genetic variants of TBEV have been identified [6][12]. Furthermore, several studies have identified geographical clustering of specific TBEV variants within small geographic areas [6][8]. Gaumann et al for example performed phylogenetic analysis of 71 TBEV found in I. ricinus in Switzerland and identified 10 phylogenetic clades of closely related TBEV, some of which showed regional clustering [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation